The Introduction of Open and Free Academic Courses in Conservation of Cultural Heritage in Greece - Anna Karatzani; Alexandros Tagoulis; Vasilike Argyropoulos; Athina Alexopoulou; Stamatis Boyatzis; Maria Chatzidaki (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The 4-year Bachelor Degree in Conservation-Restoration at the Technological Educational Institute (TEI) of Athens has the difficult task of preparing its students to become professional Conservator-Restorers with knowledge and skills in six specializations of either archaeological (objects) conservation or in conservation works of art. Thus, the academic staff of the Department has the challenge to prepare its students to be qualified in practice and knowledge of many specializations of conservation of Cultural Heritage (CH) within its 4 year program. To meet this demand, many members of the academic staff are participating in a project co-financed by Greece and the European Union (European Social Fund) called ‘Open Academic Courses’ (2013-2015). The goal is to prepare their course material in Greek as freely accessible digital educational content in the form of thirteen PowerPoint lectures with or without video lectures per course offered via the open source eLearning platform ‘Open eClass’ hosted by the TEI of Athens. The paper describes how the courses were prepared, the challenges involved in its preparation, as well as the benefits to the students.